Chiral amido-oxazoline functionalized MCM-41: A sustainable heterogeneous catalyst for enantioselective Kharasch–Sosnovsky and Henry reactions - Niloofar Tavakoli; Hamid Arvinnezhad; Shiva Majidian; Mahsa Mahramasrar; Khosrow Jadidi; Saadi Samadi (Heliyon)
In this study, a series of chiral amido-oxazoline ligands was synthesized with a primary focus on immobilizing the most effective ligands on MCM-41 mesoporous material. Following several attempts, the para-nitro group of the chiral amido-oxazoline ligands was successfully reduced to amino group, enabling their immobilization on MCM-41. The resulting chiral heterogeneous amido-oxazoline ligands were characterized using various techniques, including FT-IR, XRD, TGA, SEM, TEM, EDX, and BET-BJH, confirming the successful immobilization of the amido-oxazoline ligands. A comparison of the efficiency of the homogeneous and heterogeneous amido-oxazoline-based ligands in the Kharasch-Sosnovsky and Henry reactions revealed better performance of the heterogeneous ligand. The immobilized amido-oxazoline-copper complexes exhibited remarkable catalytic activity, achieving excellent yields and enantioselectivities (up to 88 % ee) in the Kharasch-Sosnovsky reaction, and delivering excellent yields with moderate enantioselectivities in the Henry reaction. Notably, the Henry reaction proceeded with moderate diastereoselectivity, favoring the syn diastereomer, under solvent-free conditions, highlighting the sustainability of the process. The heterogeneous nature of the catalysts facilitated effortless recovery and efficient reusability.